A Method for Using GSM Technology and SCADA Systems to Monitor and Control Decommissioned and Partially Decommissioned Railway Stations - Alexandru-Florian Popov; Dominic Mircea Kristaly; Dragoș-Vasile Bratu; Maria-Alexandra Zolya; Sorin-Aurel Moraru (Applied Sciences, 2023)
Railway systems are sometimes faced with the necessity of decommissioning railway stations due to issues in the electricity supply system, control system failures, or a decrease in train traffic. In order for fully or partially decommissioned stations to maintain functionality and turnout availability, the researchers propose the use of a computer system utilizing GSM technology. Using AES-encrypted SMS messages, GSM signaling can be applied to a wide range of electrical equipment at decommissioned stations, enabling monitoring and control of these installations remotely, as well as allowing for integration into an existing SCADA system. This study attempts to estimate the reduction in total delays and operating cost that would arise when implementing this control system in a low-resource setting. An impact and cost analysis was performed on a rail section with partially decommissioned stations (Brașov–Codlea, Romania), to ascertain whether this control method would result in significant delay and cost reductions. The analyzed data show that the proposed control system can significantly reduce delays and costs on railway lines with decommissioned stations, thus allowing for a more efficient use of resources. By leveraging technology to monitor and control electrical installations remotely, the need for physical presence at the decommissioned station is eliminated. Overall, the research described represents a significant step towards the more efficient and safe use of railway infrastructure, and could potentially lead to the reactivation of previously decommissioned stations, providing benefits for both passengers and freight transport operators.